PENGARUH STORE ATMOSPHERE, STORE LOCATION, dan IN-STORE EMOTIONAL EXPERIENCES TERHADAP STORE ATTITUDE PADA SPECIALITY STORE â€œSTROBERIâ€ TUNJUNGAN PLAZA SURABAYA - LISANTHI, WINDA (Universitas Katolik Widya Mandala Surabaya, 2013)
The purpose of this research is knowing the effect of store atmosphere towards in-store emotional experiences, the effect store location towards store attitude, the effect in-store emotional experiences towards store attitude and store atmosphere towards store attitude through in-store emotional experiences at speciality store â€œStroberiâ€ Tunjungan Plaza Surabaya. Amount samples in this study is 150 samples. Data analysis technique used is a Structural Equation Model (SEM) with LISREL 8.70 program. The results of this study indicate that store atmosphere has a positive effect towards in-store emotional experiences, store location has a positive effect towards store attitude, in-store emotional experiences has a positive towards store attitude, and store atmosphere has a positive towards store attitude through in-store emotional experiences.